Transmission of tomato fruit blotch virus by the tomato russet mite: epidemiological implications for an emerging/re-emerging tomato disease - Sabrina Bertin; Anna Sybilska; Marta Luigi; Franca Tarchi; Donatella Goggioli; Anna Taglienti; Davide Luison; Francesco Faggioli; Sauro Simoni; Mariusz Lewandowski; Antonio Tiberini (Scientific Reports)
Abstract The tomato russet mite (TRM), Aculops lycopersici (Trombidiformes: Eriophyoidea), was recently suspected to be the vector of tomato fruit blotch virus (ToFBV; Blunervirus solani), a newly identified kitavirus infecting tomato cultivation worldwide. Tomato fruit blotch virus represents a serious threat to tomato crops, and its transmission needs to be clarified to achieve better disease control and monitoring. Two independent transmission trials were performed by inoculating 20 and 18 healthy tomato plants with viruliferous TRM specimens. A total of 13 plants (34.21%) resulted to be infected at different time points across an 18-week period, and showed foliar symptoms consisting of slight mosaic, chlorotic areas and discoloration that were solely attributed to ToFBV infection. This is the first evidence of the ability of TRM to acquire and transmit ToFBV from and to tomato plants. The highest rate of infection and the peak of virus titre occurred late, between ten and 14 weeks after inoculation. Afterwards, a general decrease in virus infection was recorded, in association with two opposite phenological responses in the host plants that worsened or improved their vegetative status. The involvement of the eriophyid vector and the limited adaptation of ToFBV to tomato are possible explanations for such slow and erratic infection dynamics.